1993
DOI: 10.1111/j.1365-2559.1993.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Signet ring cell differentiation in adenocarcinoma of the prostate: a study of five cases

Abstract: Signet ring cell differentiation in adenocarcinoma of the prostate is uncommon. In a review of 200 cases of prostatic carcinoma, we identified five cases with this change, all in moderately to poorly differentiated prostatic carcinomas. The signet ring cells in prostatic carcinoma contain an intracytoplasmic lumen, shown on electronmicroscopy to be lined by microvilli. Transition stages were seen from solid to acinar to signet ring cells to mucinous variants. We believe that this change is part of the spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 15 publications
2
39
0
2
Order By: Relevance
“…A minority of cells may be mucin-positive, but generally with weak staining. 34 The tumor cells are PSA-and PAP-positive. Signet ring cell areas are considered grade 5.…”
Section: Signet Ring Cell Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…A minority of cells may be mucin-positive, but generally with weak staining. 34 The tumor cells are PSA-and PAP-positive. Signet ring cell areas are considered grade 5.…”
Section: Signet Ring Cell Carcinomamentioning
confidence: 99%
“…Designation as a signet ring cell carcinoma is restricted to those cases where the signet ring cells make up over 25% of the tumor volume, although a wide range of definitions have been applied. [31][32][33][34][35][36][37][38] Clinically, these tumors are typically of advanced stage at the time of diagnosis. 15,26,36 Serum PSA is usually significantly elevated.…”
Section: Signet Ring Cell Carcinomamentioning
confidence: 99%
“…These cells are more frequently seen focally within otherwise high-grade prostate cancers and should be considered as part of the Gleason scoring [3]. But, Guerin and colleagues [1] suggested that SRCC should be classified as a variant of high-grade adenocarcinoma rather than a separate histologic classification. The largest series to date has shown poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated to occur in 2.5% of cases of prostate adenocarcinoma [1]. Prostate SRCC is diagnosed by eliminating of other organs such as colon and stomach, pancreas, breast, thyroid and bladder.…”
Section: Case Reportmentioning
confidence: 99%
“…Olgumuzda da LHRH uygulandıktan altı ay sonra yapılan pasaj TUR patalojisi taşlı yüzük hücreli adenokarsinom gelmesi, bizleri de antihormonal tedaviye bağlı bir durum olabileceğini düşündürdü ancak yapılan immünhistokimyasal boyama ile bu durum dışlandı. Leucocyte common antigen (LCA), alpha-smooth muscle actin (ASMA), sitokeratin 7 ve 20'nin negatif ve PSA'nın pozitif olması tanıyı güçlendirir (3)(4)(5)(6). Carcinoembryonic antigen (CEA), literatürdeki vakaların %20'sinde pozitif olarak bulunmuştur (10).…”
Section: Discussionunclassified